2008
DOI: 10.1111/j.1399-3054.2008.01089.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of gene expression system in a marine diatom using viral promoters of a wide variety of origin

Abstract: Promoter sequences of the cytomegalovirus (PCMV), the rous sarcoma virus long terminal repeat (PRSV-LTR) and the cauliflower mosaic virus 35s (PCaMV35s) were ligated with the beta-glucuronidase (GUS) gene, uidA, and were introduced into cells of the marine diatom, Phaeodactylum tricornutum. Transformants were selected on a 100 mg l(-1) Zeocin plate, and Zeocin-resistant clones were further selected by the occurrence of GUS activity. Two to 10 GUS-positive clones were obtained, and GUS activities in these trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 28 publications
0
16
0
1
Order By: Relevance
“…Although there is some information available regarding the functionality of heterologous regulatory DNA sequences or promoters in diatoms (Brakemann et al, 2008; Dunahay, Jarvis & Roessler, 1995; Falciatore et al, 1999; Kadono et al, 2015; Sakaue, Harada & Matsuda, 2008), all the widely utilised transformation systems for the diatoms Phaeodactylum tricornutum (Falciatore et al, 1999; Zaslavskaia et al, 2000), Cylindrotheca fusiformis (Fischer et al, 1999) and Thalassiosira pseudonana (Poulsen, Chesley & Kröger, 2006) employ promoters derived from the respective target organism. The availability of genome sequence data for several diatoms (Armbrust et al, 2004; Bowler et al, 2008; Lommer et al, 2012) allows the identification of putative promoter sequences that can be tested regarding their usability.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is some information available regarding the functionality of heterologous regulatory DNA sequences or promoters in diatoms (Brakemann et al, 2008; Dunahay, Jarvis & Roessler, 1995; Falciatore et al, 1999; Kadono et al, 2015; Sakaue, Harada & Matsuda, 2008), all the widely utilised transformation systems for the diatoms Phaeodactylum tricornutum (Falciatore et al, 1999; Zaslavskaia et al, 2000), Cylindrotheca fusiformis (Fischer et al, 1999) and Thalassiosira pseudonana (Poulsen, Chesley & Kröger, 2006) employ promoters derived from the respective target organism. The availability of genome sequence data for several diatoms (Armbrust et al, 2004; Bowler et al, 2008; Lommer et al, 2012) allows the identification of putative promoter sequences that can be tested regarding their usability.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have demonstrated that the endogenous ptca1 and ptca2 showed, respectively, about 25 and 3.5 times increase in their transcript levels by acclimating from 5% CO 2 to air Harada et al, 2006) and the reporter construct of Pptca1 fused with the b-glucuronidase (GUS) gene, uidA, was a quantitative indicator for the CO 2 response of Pptca1 in transformant cells expressing this fusion reporter construct (Harada et al, , 2006Sakaue et al, 2008, Ohno et al, 2012. We thus used this GUS reporter system to identify the critical element required for switching Pptcas activity in response to light/CO 2 by means of sequence manipulations of heterologously introduced promoter constructs.…”
Section: Requirement Of Light For Co 2 -Responsive Regulation Of the mentioning
confidence: 99%
“…The same strategy, using HSP70 fused to CAb (chlorophyll-binding protein), was reported in the charophyte Closterium peracerosum (Abe et al, 2011). Usual plant promoters, such as the cauliflower mosaic virus 35S with Ubiquitin-Ω, have been also tested in some microalgae (Kumar et al, 2004, Jarvis and Brown, 1991, Chen et al, 2001, Wang et al, 2007, and recently the 35S promoter demonstrated efficiency in the diatom P. tricornutum (Sakaue et al, 2008), Chlorophytes Haematococcus sp. (Kathiresan et al, 2009) and Dunaliella bardawil (Anila et al, 2011) and the Heterokonta Nannochloropsis sp.…”
Section: Identification Of Promoter Sequencesmentioning
confidence: 95%